1993
DOI: 10.1002/eji.1830230604
|View full text |Cite
|
Sign up to set email alerts
|

Synovial IgG rheumatoid factors show evidence of an antigen‐driven immune response and a shift in the V gene repertoire compared to IgM rheumatoid factors

Abstract: We have established IgG rheumatoid factor (RF)-secreting hybridoma cell lines from the synovial tissues of three patients from whom we have previously characterized several IgM RF. The IgG RF bind human and rabbit IgG and form intracellular complement-fixing complexes indicative of a self association process in vivo. Nucleotide sequence analysis revealed that two IgG RF used VHIII gene segments, while one used a VHI gene segment. The VL gene usage consisted of a V kappa 1, a V lambda 2 and a V kappa 4/V kappa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
7
28
0
Order By: Relevance
“…These observations support our previous studies of V H gene expression within IgM-and IgGproducing synovial hybridomas and studies of synovial RF by other investigators [3,4,34]. The current data disagree with a previous investigation in which a cDNA library established from the synovium of an RA patient was used [20].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These observations support our previous studies of V H gene expression within IgM-and IgGproducing synovial hybridomas and studies of synovial RF by other investigators [3,4,34]. The current data disagree with a previous investigation in which a cDNA library established from the synovium of an RA patient was used [20].…”
Section: Discussionsupporting
confidence: 78%
“…Two alternative mechanisms, antigen-driven and polyclonal activation, have been suggested as possible causes of sustained B cell activation and autoantibody production [2]. In recent years it has been argued that the finding of mutated RF and the production of autoantibodies to local antigens in the synovium, such as collagen type II, implicate antigen-driven immune responses in disease pathogenicity [3][4][5]. Other studies, however, have suggested that enrichment of B lymphocyte sub-populations characterized by the ability to produce natural autoantibodies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Abs responding following a third or fourth Ag exposure are not identical to those responding to a primary or secondary exposure. This has been shown to be true in a number of systems, including the haptens (4-hydroxy-3-nitrophenyl)acetyl (NP) and 2-phenyl oxazolone (6,7), as well as for respiratory syncytial virus (8), influenza hemagglutinin (9), and rheumatoid factor (10).…”
mentioning
confidence: 95%
“…Peripheral blood mononuclear cells (PBMC) were prepared from 20 ml heparinized blood by centrifugation on FicollHypaque, Genomic DNA was prepared and purified [23], The following oligonucleotide primers were used for polymerase chain reaction (PCR) amplification: VH1/7 5'CTA-GGTCGACCCTCAGTGAAGGTYTCCTGCAAGGC3'; JH4 identical to the published sequence of the somatically mutated VKIV light chain of the IgA RF-producing hybridoma P61B27 [14] derived from peripheral blood lymphocytes (PBL) of the same patient in October 1990 and in December 1992, They are compared with the RF sequence (P61B27) [14], with the VKIV germ-line sequence (VK4gl) [17] and with clone 92KL51B, Nucleotide exchanges that were each found in only one of the clones that were sequenced, most probably due to misincorporation by the Taq polymerase, are indicated by #, Identities are indicated by dashes. Numbering is according to Klobeck [17], numbers at the ends of the lines designate nucleotides, numbers above the sequence designate amino acids, + designates additional amino acids in CDRl characteristic for the VKIV family.…”
Section: Dna Preparation and Amplificationmentioning
confidence: 99%
“…The cross-reacting idiotypes (CRI) and V-genes often found to be involved are distinct from those expressed in the naturally occurring RF [6], There is evidence that the pathological RF in RA undergo affinity maturation and are the product of an antigen-driven response [10][11][12][13][14]. Especially IgG RF isolated from synovial tissue have been shown to be encoded by somatically mutated V-region genes [11,14] and thus resemble RF characterized in the MRL/lpr mouse model of RA [15]. However, the question of how long single RF-producing clones persist in RA patients has not been addressed so far.…”
Section: Introductionmentioning
confidence: 99%